Development of Audio Visual Learning Media Material on The Distribution of Flora and Fauna in Class XI at SMAN 6 Palu City - Nur Ainun; Rendra Zainal Maliki (LPPM Universitas Tadulako, 2022)
This research aims to: 1) develop valid audio-visual learning media at SMAN 6 Palu. 2) find out students' perceptions of audio-visual media at SMAN 6 Palu. The development method in this research is research and development (R&D) with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. The research and development procedure consists of five steps but only three are carried out. The object of this research trial was class XI students at SMAN 6 Palu. The research instruments used in data collection were divided into 2, namely validity test instruments in the form of validation sheets by media experts and experts. The data collection techniques used in this research were validity tests and practicality tests. The data obtained was then analyzed using descriptive analysis. Data from validation results in the form of suggestions and assessments as a basis for improving and perfecting the learning media products being developed. Based on the validation results obtained, the material expert validation data obtained with a percentage of 87% was in very good qualifications for use, and the validation results of learning media experts with a percentage of 91% were in very good criteria for use. The results of small group trials obtained an average of 77% with appropriate criteria. The field test results obtained were 73% with appropriate criteria. Thus, this product can be used as teaching material in schools which has an overall average score of 83% with very appropriate criteria and does not need to be revised. Then according to students, with audio-visual learning media, they understand the material in the learning process better.